Vulgar ethics for public administration - Mainzer, Lewis
Though committed to ethical concerns in the teaching and practive of public administration, this article warns how little bans there is foran evidently burgeoning confidence in the ability to prepare others to do good actions. Yet skeptiasm is not despair, and ethical reflection is surely required. Ethics may paradoxically be both the easiest and the most difficult element of public administration to teach. The article examines the possibilities of teaching a "vulgar ethics" of public administration. Reproduced
Keywords: Public Administration; Professional Ethics; Ethics; Professional Ethics